2016
DOI: 10.1038/srep36632
|View full text |Cite
|
Sign up to set email alerts
|

Ocular toxoplasmosis: susceptibility in respect to the genes encoding the KIR receptors and their HLA class I ligands

Abstract: The objective of this study was to investigate the influence of the genes encoding the KIR receptors and their HLA ligands in the susceptibility of ocular toxoplasmosis. A total of 297 patients serologically-diagnosed with toxoplasmosis were selected and stratified according to the presence (n = 148) or absence (n = 149) of ocular scars/lesions due to toxoplasmosis. The group of patients with scars/lesions was further subdivided into two groups according to the type of ocular manifestation observed: primary (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…If a given HLA association is attributable to NK cells rather than CD8 + T cells, then other HLA class I molecules with similar KIR-binding properties should be similarly protective/detrimental (in the context of the relevant KIRs). This pretext forms the basis of classical KIR-HLA analyses (30)(31)(32)(33). We investigated this possibility for each of the HLA class I alleles included in this study (HLA-B*57 and HLA-B*35Px in the HIV-1infected (Functional KIR3DS1-) IAVI cohort; HLA-A*02:07, HLA-C*08, and HLA-B*54 in the HTLV-1-infected Kagoshima cohort; and HLA-B*57 in the HCV-infected cohort).…”
Section: Primary Hla Class I Associations Are Unlikely To Be Attribut...mentioning
confidence: 99%
“…If a given HLA association is attributable to NK cells rather than CD8 + T cells, then other HLA class I molecules with similar KIR-binding properties should be similarly protective/detrimental (in the context of the relevant KIRs). This pretext forms the basis of classical KIR-HLA analyses (30)(31)(32)(33). We investigated this possibility for each of the HLA class I alleles included in this study (HLA-B*57 and HLA-B*35Px in the HIV-1infected (Functional KIR3DS1-) IAVI cohort; HLA-A*02:07, HLA-C*08, and HLA-B*54 in the HTLV-1-infected Kagoshima cohort; and HLA-B*57 in the HCV-infected cohort).…”
Section: Primary Hla Class I Associations Are Unlikely To Be Attribut...mentioning
confidence: 99%
“…Likewise, the TNF-α gene polymorphism (2308G/A) do not seem to be associated with OT development and recurrences [ 58 ]. Similarly, Ayo et al found that the presence of the -KIR3DS1/KIR3DL1+/Bw4-8-80Ile+ combination was a protective factor against recurrences (OR: 0.13; 95% CI 0.03–0.45) [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the influence of KIR with their respective ligands, patients and controls were classified into groups according to their HLA ligands: HLA-A3 or A11, HLA-Bw4 (Bw4-80Ile and Bw4-80Thr) (20,21) and HLA-C ligand of the C1 or C2 group. (22) The KIR haplotype groups (AA, Bx) and genotype ID were obtained from the Allele Frequency Net Database (http://www.allelefrequencies.…”
Section: Discussionmentioning
confidence: 99%